Effect of casing and supplementation on yield of milky mushroom (Calocybe indica) - and RAJNISH KUMAR GAUTAM, MANDVI SINGH, A.K. SINGH (Indian Phytopathology, 2007)
Trials were conducted to see the effect of casing and supplementation in casing at the time of its application on productivity of milky mushroom (Calocybe indica P&C). Six casing mixtures viz, SC (spent compost) + FYM (Farm Yard Manure) + sand + GS (garden sOil) (1:1:1 :1), SC + FYM (2:1), SC alone, SC +FYM (1:1), SC + FYM (1:2) and FYM alone were taken. Soil was chemically sterilized before casing application. The casing prepared using SC, FYM, sand and GS in the ratio of 1:1:1:1 gave the highest yield as well as the maximum number of sporophores. In another trial casing mixture of SC + FYM + sand + GS (1:1:1:1) was supplemented with grain spawn @ 2 per cent and soybean meal @ 2 per cent, 3 per cent and 4 per cent. Supplementation of soybean meal @. 4 per cent produced better yield as well as number of fruit bodies than other treatments.